The Effect of Soil Radioactivity in Pollution - Abbas Hosseini; Masoomeh Fasih zaban (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: One of the sources of natural occurring radiation was soils. The purpose of article was to determine soil pollution by radiation absorbed dose rate, radium equivalent activity, external hazard index, annual gonad dose equivalent and annual effective dose equivalent. Methods & Materials: The soil samples was located in Chahbahar city in Blouchestan of Iran, was chosen for studying of radioactivity. It was collected from twenty five points, each one in three separate places with 100 meter distance (twelve in western and thirteen in eastern sites) in the region. Then, each three soil samples were mixed and dried as one sample. The radioactivity concentration was measured in soil samples by gamma spectrometer. Results: The natural radioactivity doses of soil in studied samples resulted in average absorbed dose rate, 42.92 ±4.03 nGy h-1; radium equivalent activity, 86.79±8.26 Raeq per Bqkg- the external hazard index, 1:8231.86±327.76; the annual gonad dose equivalent, 322.9±31.6 μSvh-1; and the annual effective dose equivalent 193.15μSvh-1.The results of study were compared with the international recommended values and radioactivity measurements in soils of different countries. Conclusion: The contribution of natural radioactivity in pollution of area in comparison to ICRP was low.